Effect of High Population Growth Rate on Economic Performance in Kyanamira Sub-County Kabale District Uganda. - Aijuka, Godwin (Kabale University, 2025)
The study examined the effect of the population growth rate on economic performance in the Kyanamira sub-county Kabale district of Uganda. The objectives of the study were; to find out the causes of a high population growth rate, to examine the implications of population growth on economic performance, and to establish the relationship between population growth and economic performance. A descriptive research design was used and data was collected using interviews and questionnaires. The study results on causes of high population growth in Kyanamira sub-county Kabale district, the highest number of the respondents mentioned early marriage while the least number of the respondents mentioned negative attitude towards family planning. The study results on the implications of population growth on economic performance in Kyanamira sub-county Kabale district, the highest number of respondents mentioned discouraged saving and investments which results in low incomes, and the lowest number of respondents talked of how high population growth affected the efficiency of developing countries and their political system. The study results on the relationship between population growth and economic performance in Kyanamira sub-county Kabale district, the study findings revealed that there is a strong relationship between population growth and economic performance. The study recommended that family planning programs should be designed to provide information, services, and modern means of fertility control to those who are interested and the study recommended that the government should use several methods to control high population growth such as one or two children per family policy, girl child education through giving them scholarships.